Cost‐effectiveness of liver transplantation in methylmalonic and propionic acidemias. Issue 9 (25th August 2015) - Li, Meng; Dick, Andre; Montenovo, Martin; Horslen, Simon; Hansen, Ryan
<x xml:space="preserve">Abstract</x> Propionic acidemia (PA) and classical methylmalonic acidemia (MMA) are rare inborn errors of metabolism that can cause early mortality and significant morbidity. The mainstay of disease management is lifelong protein restriction. As an alternative, liver transplantation (LT) may improve survival, quality of life, and prevent further neurological deterioration. The aim of our study was to estimate the incremental costs and outcomes of LT versus nutritional support in patients with early‐onset MMA or PA. We constructed a Markov model to simulate and compare life expectancies, quality‐adjusted life years (QALYs), and lifetime direct and indirect costs for a cohort of newborns with MMA or PA who could either receive LT or be maintained on conventional nutritional support. We conducted a series of 1‐way and probabilistic sensitivity analyses. In the base case, LT on average resulted in 1.5 more life years lived, 7.9 more QALYs, and a savings of 582, 369 for lifetime societal cost per individual compared to nutritional support. LT remained more effective and less costly in all 1‐way sensitivity analyses. In the probabilistic sensitivity analysis, LT was cost‐effective at the 100, 000/QALY threshold in more than 90% of the simulations and cost‐saving in over half of the simulations. LT is likely a dominant treatment strategy compared to nutritional support in newborns with classical MMA or PA. Liver Transpl 21:1208‐1218, 2015. © 2015 AASLD.